1996
DOI: 10.1089/dna.1996.15.175
|View full text |Cite
|
Sign up to set email alerts
|

A Large Variety of Alternatively Spliced and Differentially Expressed mRNAs Are Encoded by the Human Acute Myeloid Leukemia Gene AML1

Abstract: The human chromosome 21 acute myeloid leukemia gene AML1 is frequently rearranged in the leukemia-associated translocations t(8;21) and t(3;21), generating fused proteins containing the amino-terminal part of AML1. In normal blood cells, five size classes (2-8 kb) of AML1 mRNAs have been previously observed. We isolated seven cDNAs corresponding to various AML1 mRNAs. Sequencing revealed that their size differences were mainly due to alternatively spliced 5' and 3' untranslated regions, some of which were vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 38 publications
2
101
0
Order By: Relevance
“…It has previously been reported that in adults RUNX3 is highly expressed in the hematopoietic system as well as in various hematopoietic cell lines (1,10,(28)(29)(30)(31). Using adult Runx3 KO mice (25) we now report that Runx3 function is essential for the maturation of single-positive (SP) CD8 ϩ T cells.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…It has previously been reported that in adults RUNX3 is highly expressed in the hematopoietic system as well as in various hematopoietic cell lines (1,10,(28)(29)(30)(31). Using adult Runx3 KO mice (25) we now report that Runx3 function is essential for the maturation of single-positive (SP) CD8 ϩ T cells.…”
mentioning
confidence: 69%
“…In adults, Runx3 is highly expressed in spleen, thymus, and blood (1,28,29,31), whereas in embryos, it is detected in liver hematopoietic precursors and in thymocytes (20). We have previously shown (25) that targeting of Runx3 exon 2 abolished expression in thymus.…”
Section: Runx1 and Runx3 Expression In Adult Thymus Is Confined Mainlmentioning
confidence: 97%
“…X79549), yields various protected fragments corresponding to various 3Ј alternative splicing. 39 No abnormal CBFA2 transcripts could be detected in the affected family member (AF) when compared to an unaffected sibling (JF) or the HL60 and K562 cell lines. There was no significant difference in the ratios of transcripts by phosphorimaging analysis except for a relative decrease in the 417-bp fragment obtained with probe BH in the affected family member, when compared to the normal sibling and cell lines.…”
Section: Figurementioning
confidence: 99%
“…Of these, four splicing variants have potential for dominant negative activity because they lack the 3Ј transactivating domain, but retain the DNA binding domain. 39,40 These splice variants, if present in excess of the full length transcript, could have an activity similar to the leukemia-associated fusions involving CBFA2.…”
mentioning
confidence: 99%
“…AML1 encodes the a-subunit of the transcription factor PEBP2/CBFb involved in the recognition of general transcription coregulators. AML1 exhibits a complex pattern of tissue-regulated expression at the level of transcription, splicing and translation (Levanon et al, 1996). Thus far, there are four AML1-identified alternative splice isoforms, namely AML1a, AML1b, AML1 Del N and AML1c, all of which contain an RHD (Miyoshi et al, 1995;Zhang et al, 1997;Mikhail et al, 2006).…”
Section: Introductionmentioning
confidence: 99%